Kegagalan Praktik Patronase-Klientelisme pada Pemilihan Kepala Desa di Kabupaten Klaten Tahun 2019 - Juang Gagah Mardhika; Rina Martini; Fitriyah Fitriyah (Mahesa Research Center, 2021)
The study patronage-clienttelism at the level Village Head Selection is still an important concern. Therefore, this study aims to explain the phenomenon of incumbent defeat and the failure patronage-clienttelism practices in the 2019 Village Head Elections in Klaten Regency. This study uses qualitative method with case study approach in Randusari Village, Jimbung Village, and Jiwowetan Village. Data collection using interviews and documentation studies, informants are selected purposively, consisting prospective village heads, successful teams, and voters. Data analysis techniques are carried out through data collection, data reduction, data presentation and drawing conclusions. The results showed that Village Head Elections Simultaneously Randusari, Jimbung and Jiwowetan 2019 are full of patronage-clienttelism practices. The types of patronage-clienttelism used vary quite by type, as well as actors who are directly related to the electorate. The practice patronage-clienttelism in all three villages, was unable to encourage the incumbent candidate to win the election result. The challengers managed to explore the limitations and cursess that exist in the incumbent. So that it is able to change the behavior of choosing society through psychological, sociological and rational choices.